GASTRONOMIA E ESTÉTICA DO GOSTO - Paula, Daniele Kerner De; Pereira, Laura Mensch; Pereira, Elisa Gabriela Da Silva; Vieira, Eilamaria Libardoni (Salão do Conhecimento, 2018)
Revisão bibliográfica realizada durante a disciplina do curso de Nutrição